Beginners guide to gardening [ - Lewis, John , 1963- (Suffolk : Fastforward, 2006)
Tips and instructions on hand tools, greenhouses, propogation, planting out, sowing vegetable seeds, planting trees and planting in containers.
Presented by John Lewis
Keywords: Gardening; Landscape gardening; Plant propagation